Pengaruh financial distress, leverage dan capital insenty terhadap tax avoidance - Vianty Adella Santo; Cipbarani Dwi Nastiti (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of financial distress, leverage, and capital intensity on tax avoidance in manufacturing companies in the basic & chemical sektors listed on the Indonesia Stock Exchange for 2017 - 2020. This study uses secondary data. The independent variables in this study are financial distress, leverage, and capital intensity. The dependent variable used is tax avoidance. The research data was obtained from annual reports from the Indonesia Stock Exchange (IDX) in 2017 - 2020. The sampling technique used was purposive sampling. This study uses multiple regression analysis methods. The analytical tool used for hypothesis testing is SPSS 25. The results of this study indicate that the leverage variable has a positive influence on tax avoidance. The financial distress variable has a negative effect on tax avoidance. While the capital intensity does not affect tax avoidance. Public interest statement The results of this study can be used as additional knowledge or as a source of insight related to the factors that influence tax evasion behavior. The Directorate General of Taxes can provide oversight, particularly regarding tax avoidance practices following the provisions of the tax legislation. Thus, tax avoidance practices can be minimized. Article history Received 11 Aug 2022 | Revised 29 Sep 2022 | Accepted 17 Nov 2022 | Online First 18 Jan 2023